Angry Birds vs. Sudoku: How Different Types of Tasks in Multitasking Affect Ad Memory and Mind Wandering. Issue 4 (2nd October 2021) - Chinchanachokchai, Sydney; Duff, Brittany R. L.; Faber, Ronald J.
Abstract: The rise of mobile usage, as well as increasing amount of information, contributes to the individual's inattention to ads and multitasking behavior. In many situations, multitasking has taken attention away from advertising messages, leading to a decrease in message effectiveness. Nonetheless, previous research has shown a potential benefit of multitasking on memory because, in some situations, multitasking could reduce mind wandering, which is a hidden distraction in ad processing. This research compares how different types of secondary tasks (cognitive vs. perceptual) affect ad memory. The results showed that a low perceptual load secondary task increased memory about ad content while decreasing mind wandering. However, cognitive load secondary tasks did not interfere with the cognitive processing more than the control condition.